THE ROLE OF METACOGNITION STRATEGY TO ENHANCE READING COMPREHENSION - Fadilah, Fitrani Dinda; Ridwan, Natashah Mohd; Putri, Nurma Dianti; Suhendri Prayoga; Ihsan, Muhammad Taufik (Jurnal Riset dan Inovasi Pembelajaran, 2021)
Metacognitive strategy is a learning approach based on John Flavell's Metacognitive notion, which describes Metacognition as an individual's ability to freely govern cognitive processes. Students are taught to organize, manage, and evaluate their learning processes via the use of Metacognitive methods, and their critical and creative thinking abilities are strengthened as a result. This capacity must be mastered in order for pupils to feel responsible for their own learning. Teachers who include processes before, during, and after reading into the process when teaching students’ efficient comprehension skills should be conversant with this Metacognitive reading paradigm. In reading, Metacognitive tactics assist pupils in keeping track of their thoughts while they read. Students can use Metacognitive skills to help them become more autonomous learners. Teachers utilize Metacognitive reading skills with their students on a regular basis and expect them to apply them independently as well. Teachers who include the processes before, during, and after reading into the process when teaching students efficient comprehension skills should be conversant with this Metacognitive reading paradigm. In reading, Metacognitive tactics assist pupils in keeping track of their thoughts while they read. Students can use Metacognitive skills to help them become more independent learners. Teachers use Metacognitive reading skills with their students on a regular basis and expect them to apply them independently as well.